Investigating the effectiveness of the Sci-Bono outreach programme in the teaching of electrochemistry at grade 11 - Nkomo, Trust (My University, 2014)
This study was on the investigation of the effectiveness of the Sci-Bono outreach programme in the teaching of electrochemistry at grade11. Two aspects were used to measure effectiveness. The first aspect was a change in learners’ ability to answer questions before and after intervention. The second aspect was the programme’s ability to eliminate common misconceptions in electrochemistry. A sample of five schools was used in the study. At each school a pre-test was given to learners before intervention and a similarly structured and equally difficult task was given after intervention as a post-test. The marks for each learner were compared and the results for each school were analysed using a Wilcoxon signed rank test and a paired data test. Results from both methods of analysis reflected significant improvement in learners’ ability to answer questions after intervention at all five schools that made the sample of the research. A question by question analysis was also done to check a change learners’ ability to answer specific questions. Improvement in answering particular questions differed significantly, pointing out that certain concepts had been grasped better than others. Interviews were held with both learners and their teachers. These interviews were held to try and determine the extent to which misconceptions had been identified and eliminated. Pre-tests and post-test analysis reflected that one common misconception, where learners define oxidation and reduction in terms of addition and removal of oxygen was completely eliminated. Learner interviews however reflected a 75% success rate in the elimination of the misconception. Analysis of pre-tests and post-test results also showed a 75% success rate in the elimination of a misconception of the second misconception, where learners take an oxidising agent as a substance that has been oxidised and a reducing agent as a substance that has been reduced, compared to 76% from analysis of the learners’ interview results. Teacher interview results also reflected that the Sci-Bono outreach programme is to a high degree able to eliminate common misconceptions electrochemistry. From lesson observation and teacher interviews another misconception came to light. The misconception held by some learners is that ‘the oxidation number is the number of oxygen atoms in the molecule of a compound.’ This misconception was also tackled. During teachers’ interviews it emerged that all host teachers perceive the Sci-Bono Subject Matter Experts as effective in eliminating the identified common misconceptions in electrochemistry. The researcher is convinced that the Sci-Bono outreach programme improves the learners’ ability to answer questions in electrochemistry and that they address misconceptions in their teaching. The intervention however does not completely eliminate common misconceptions in electrochemistry. The Sci-Bono outreach programme is thus only effective to a certain extent in the teaching of electrochemistry at grade 11. The study also revealed that the teachers at schools expect the Sci-Bono Subject Matter Experts to have better pedagogical skills and they also expect them to bring scarce resources when they visit schools. They expect them to be able to tackle all formal and informal experiments covered in the grade11 curriculum. They believe that, in addition to enabling the elimination of misconceptions, the practicals carried out by the Sci-Bono SMEs also enhance understanding and provide practical skills to learners.
A research project submitted to the University of the Witwatersrand, Faculty of Humanities, Wits School of Education, in partial fulfilment of the requirements for the degree of Master of Science in Science Education. November 2014
Keywords: Electrochemistry.; Electrochemistry--Study and teaching (Secondary); Effective teaching.